INTERNET CENSORSHIP BY LAW: A CHALLENGE TO THE CONSTITUTIONAL RIGHT TO FREEDOM OF EXPRESSION IN THAILAND (UUM Journal of Legal Studies, 2014)
In Thailand, at present, content on the Internet is subject to a legal regulatory framework. The Ministry of Information and Communication Technology (MICT) takes a leading role in enforcing the Computer-Related Crime Act 2007 to censor content on the Internet which is deemed ‘illegal’. In this article, it is contended that the legal regulation of Internet content which Thailand adopts is problematic in several aspects. This could pose a serious threat to the constitutional right to freedom of expression of Internet users in Thailand.Keywords: Internet censorship, freedom of expression, Thailand.